Analysis of fatigue behaviour of stainless steels under hydrogen influence - D. Angelova; R. Yordanova; S. Yankova (Fracture and Structural Integrity)
Three stainless steels – ASTM 304, 316 and 316L - used in hydrogen utilization equipment are under investigation at conditions of tension-compression, rotating-bending and fretting fatigue. Fatigue tests are carried out with hydrogen charged and uncharged specimens. Hydrogen charging includes cathodic type of charging and exposure to high pressure hydrogen gas. The experiments under rotating bending and tensioncompression fatigue are conducted under different frequencies in three different laboratories: at The University of Chemical Technology and Metallurgy, Sofia, Bulgaria; at Sandia National Laboratory, California and The University of Tufts, Medford, Massachusetts, USA; The HYDROGENIUS Institute at Kyushu University, Japan. The fretting fatigue tests are presented by The HYDROGENIUS Institute at Kyushu University, Japan. The obtained results are presented in Wöhler curves complemented by plots "Short fatigue crack length– Number of cycles" and “Tangential force coefficient–Stress amplitude”. The found fatigue characteristics are analyzed and compared at different loading conditions, showing the best performance of Steel 316L.